Rational engineering of Apoferritin-based nanoparticles for drug delivery - Crowhurst, Samuel (2025)
Effective drug delivery remains a major challenge in treating diseases like cancer, where targeted delivery systems are critical for maximizing efficacy and minimizing side effects. Drug delivery systems (DDS) offer a promising solution, and apoferritin, a protein-based nanoparticle, has shown considerable potential as a DDS due to its biocompatibility and capacity for drug encapsulation. However, the effectiveness of apoferritin for drug delivery is limited by the leakage of small drug molecules through its surface pores, which prevents drug accumulation at a target site. Addressing this challenge through the structural engineering of apoferritin’s pores could expand its utility, enabling it to encapsulate a wider range of therapeutic agents. This thesis aims to provide directives for potential pore modifications to optimise ferritin as a versatile nanocarrier capable of retaining even small, leakage-prone drugs. This is achieved through the use of in silico molecular dynamics simulations to minimise small molecule drug leakage by mutating the ferritin threefold and fourfold surface pores. The analysis of these modifications is supported by a streamlined protocol for the in silico analysis of mutants focusing on their structural stability and ability to minimise pore leakage. Preliminary experimental work is provided from which future work can validate these results in vitro.